ERRORS OF LINGUISTICS COMPONENTS FOUND IN THE BACKGROUND OF THE STUDY OF THE S1 STUDENTS’ THESES (RETAIN, 2014)
ERRORS OF LINGUISTICS COMPONENTS FOUND IN THE BACKGROUND OF THE STUDY OF THE S1 STUDENTS’ THESES Dewi Anggraini English Education Department, Language and Arts Faculty, Surabaya State University. email: dedewanggara@ymail.com Prof. Dr. Susanto, M.Pd. English Education Department, Language and Arts Faculty, Surabaya State University. Abstrak Membuat kesalahan adalah salah satu hal yang tak dapat dihindari di dunia, terutama di pempelajaran bahasa, karena ini adalah bagian yang alami dari proces pembelajaran. Kesalahan siswa dapat diamati, dianalisis, dikelompokkan, dan dipelajari menggunakan error analysis dan hasil dari analisis tersebut dapat menunjukkan perkembangan siswa dalm penguasaan bahasa dan membantu guru dalam proses belajar dan mengajar. Penelitian ini menganalisa komponen bahasa dalam latar belakang permasalahan dalam skripsi mahasiswa jurusan Bahasa Inggris Universitas Negeri Surabaya. Peneliti menggunakan metode penelitian deskriptif kualitatif karena tujuan dari penelitian ini adalah untuk mendeskripsikan gambaran dari kesalahan morfologikal, leksikal, sintaktik, dan mekanikal yang dibuat oleh mahasiswa dalam latar belakang permasalahan skripsi mereka. Peneliti mengambil enem skripsi dari tiga kelompok. Peneliti mengambil dua skripsi dari mahasiswa yang lulus lebih cepat (kurang dari empat tahun), dua skripsi dari mahasiswa yang lulus tepat waktu (empat tahun), dan dua skripsi dari mahasiswa yang lulus lambat (lebih dari empat tahun). Kemudian, dalam menganalisa dan menafsirkan data, peneliti menggunakan Ferris’s error analysis model sebagai acuan. Hasil dari penelitian menunjukkan bahwa: 1) Untuk kesalahan morfologikal, peneliti menemukan bahwa dari semua macam kesalahan morfologikal, kesalahan yang paling utama adalah subject-verb agreement dan kesalahan artikel/determiner, terutama kesalahan penggunaan artikel kosong (Ø) untuk the. 2) Untuk kesalahan leksikal, siswa hanya membuat sedikit kesalahan dalam preposisi dan sub kategori lain di kesalahan leksikal. Ini menunjukkan bahwa siswa telah menguasai kosa kata Bahasa Inggris untuk menyusun kalimat yang benar. 3) Untuk kesalahan sintaktik, peneliti menemukan bahwa siswa membuat kesalahan paling banyak di penghilangan kata dan run-on sentence. Dan 4.) untuk kesalahan mekanikal, peneliti menemukan bahwa kealahan tanda baca, terutama dalam penggunaan koma, adalah kesalahan yang paling banyak muncul diikuti kesalahan kapitalisasi. Kata Kunci: Error Analysis, Kesalahan Morfologikal, Kesalahan Leksikal, Kesalahan Sintaktik, Kesalahan Mekanikal. Abstract Making errors is one of the most inevitable things in the world, especially in language learning, since it is a natural part of learning process. Students’ errors can be observed, analyzed, classified, and studied by using error analysis and the result of analysis can indicate the students’ development in mastering the language and help the teachers in teaching and learning process. This study analyzes the linguistics components in the theses’ background of the study of the English Department’s students in Surabaya State University. The researcher used descriptive qualitative as the research design because the objectives of this study were to describe the profile of morphological, lexical, syntactic, and mechanical errors made by the university students in their theses’ background of the study. The researcher took six theses from three groups randomly. She took two theses from the students who graduated earlier (less than four years), two theses from the students who graduated on time (four years) and two theses from the students who graduated late. Then, in analyzing and interpreting the data, the researcher used Ferris’s error analysis model as the guidline.The findings of this study revealed that: 1) For the morphological error, the researcher found that from all kind of errors in morphological error, the most problematic errors were subject-verb agreement errors and article/determiner errors, especially for misused of zero article (Ø) for the. 2) For the lexical error, the students only made few preposition errors and other subcategories errors in lexical error. It indicated that the students had already mastered the English vocabularies to construct the appropriate sentences. 3) For the syntactic error, she found that the students made the most errors in omitted word and run-on sentence. And 4) for the mechanical error, she found that punctuation error, especially in using comma, was the most problematic error followed by capitalization error. Keywords: Error Analysis, Morphological Error, Lexical Error, Syntactic Error, Mechanical Error. introduction Making errors is one of the most inevitable things in the world, especially in language learning, since it is a natural part of learning process (Makino: 1993). In the language learning process, the students continuously explore and improve their knowledge about the rules of the target language. Consequently, when they do not complete or lack of the knowledge, they will make errors. According to Brown (2000: 217), an error occurs because the students do not know what is correct and it cannot be self-corrected. They need helps or feedbacks from the teacher to correct it. Thus, an error is no longer seen as a bad thing which has to be avoided in language learning process as in the past since it can indicate the students’ development in mastering the language and help the teachers in teaching and learning process. Maicusi, T., Maicusi, P., and Lopez (2000) state that errors take place when the deviation arises as a result of lacking of knowledge. Then, Choiriyah (2007) defines errors as any deviation from a selected norm of language performances, no matter the possibility of the characteristic or causes of the deviation. In a few words, from the definitions above, it can be concluded that errors are the result of the deviation from the target language’s norms and lack of knowledge about the target language itself. Brown (2000: 217) states that error and mistake are different. He states that a mistake occurs because of slip or lack of attention or carelessness in utilizing the language system and it can be self-corrected whereas an error occurs since the learner does not know what is correct, and it cannot be self-corrected. In the other hand, Ellis (2007:18) states that the difference between an error and a mistake may not be clear since the learners sometimes constantly use a feature in some contexts and constantly fail to use it in others. Error is categorized as local and global error. Heaton (1988: 149) states that local errors are errors which do not cause significant trouble and misunderstanding for the readers in comprehending the sentences (e.g. misuse of articles, omission of preposition, etc.), whereas global errors are errors which influence the overall structure of the sentences and make the readers get difficulty to understand the sentence (misuse of connective, omission of relative pronoun). According to Brown (2000: 223-227), there are four sources of errors. They are interlingual transfer, intralingual transfer, context of learning, and communication strategies. 1. Interlingual transfer is caused by the interference of the mother-tongue; it makes students have a tendency to copy every word or grammar rules of their native language into the target language. 2. Intralingual transfer is the negative transfer of items within the target language or the incorrect generalization of the target language’s rule. 3. Context of learning can be called as false concept, the learner makes faulty hypothesis because of misleading explanation from the teacher or faulty presentation of the structure of word in textbook. 4. Communication strategy is the learning style of the learners; they use wrong strategies when getting their massages, so it causes the errors. Then, according to Touchie (1986: 77-79), there are two main sources of errors in second language learning. The first source is interference from the native language/ mother-tongue. Errors due to the influence of the native language are called interlingual errors. Interlingual errors are also called transfer or interference errors. The second source is intralingual and developmental factors. Intralingual and developmental errors are due to the difficulty of the second/target language. Intralingual and developmental factors include the following: Simplification: Learners often choose simple forms and constructions instead of more complex ones. An example of simplification might involve the use of simple present instead of the present perfect continuous. 2. Overgeneralization: This is the use of one form or construction in one context and extending its application to other contexts where it should not apply. Examples of overgeneralization include the use of buyed and goed as the past tense forms of buy and go. It should be noted that simplification and overgeneralization are used by learners in order to reduce their linguistic burden. 3. Hypercorrection: Sometimes the keen efforts of teachers in correcting their students' errors induce the students to make errors in otherwise correct forms. 4. Faulty teaching: Sometimes it happens that learners' errors are teacher-induced ones, i.e., caused by the teacher, teaching materials, or the order of presentation. This factor is closely related to hypercorrection above. Also, it is interesting to note that some teachers are even influenced by their pupils' errors in the course of long teaching. 5. Fossilization: Some errors, especially errors in pronunciation, persist for long periods and become quite difficult to get rid of. Examples of fossilized errors are the lack of distinction between /p/ and /b/ in English produced by these learners. 6. Avoidance: Some syntactic structures are difficult to produce by some learners. Consequently, these learners avoid these structures and use instead simpler structures. 7. Inadequate learning: This is mainly caused by ignorance of rule restrictions or under differentiation and incomplete learning. An example is omission of the third person singular s as in: He want. 8. False concepts hypothesized: Many learners' errors can be attributed to wrong hypotheses formed by these learners about the target language. For example, some learners think that is is the marker of the present tense. So, they produce: He is talk to the teacher. Similarly, they think that was is the past tense marker. Hence they say: It was happened last night. Brown (2000: 218) states that errors can be observed, analyzed, classified, and studied by using error analysis. James (1998) as cited in Gustilo and Magno (2012) defines error analysis as the analyses of the errors made by L2 learners by comparing and explaining the learners’ norms with the target language norms. Then, Yang (2010) states that “error analysis is the process of determining the incidence, nature, causes and consequences of unsuccessful language”. Furthermore, Hariri (2012) defines error analysis as a systematic procedure which includes collecting, identifying, describing, explaining, and evaluating errors from a collection of language learner data by analyzing and comparing it to the target language. Hence, it can be concluded that error analysis can discover the students’ weakness in the process of language learning through studying the students’ errors. By conducting it, the teachers can be sensitive to their students’ errors and notice what kind of errors which the students often make. Then, they can modify their teaching materials in order to adapt to the students’ needs. According to Ellis (2007: 15-20), there are four steps in analyzing students’ errors. They are identifying, describing, explaining, and evaluating errors. 1. Identifying Errors In identifying errors, the researcher compares the sentences which are produces by learners with the correct sentences in the target language. If the sentences are judged incorrect for the target language or inappropriate for a particular context, they are categorized as errors. 2. Describing Errors In this step, all errors are described and classified into types. The researcher may categorize errors into types, such as grammatical, phonological, lexical, or morphological categories. 3. Explaining Errors In this step, the researcher tries to explain why errors occur. It enables the teachers to identify the process in the students’ mind which have caused errors to occur. 4. Evaluating Errors In evaluating step, the researcher measures the comprehensibility of students’ writing. Here, he/she can know whether the students’ errors are included to global or local error. According to Touchie (1986:76), language learning errors involve all linguistics components. The linguistics components include phonology, morphology, lexicon, syntax and orthography. Then, errors in these linguistics components are called as phonological, morphological, lexical, syntactic, and orthography errors. When the teachers or the researchers want to analyze the students’ composition, they can focus on analyzing the morphological, the lexical, the syntactic, and the orthography errors. Here, the phonological error is excluded since it does not deal with the students’ composition. It is only analyzed when they want to investigate the students’ speaking ability. Analyzing linguistics components of students’ compositions is very important because linguistics components have an important role in a composition. Heaton (1988: 146) states that linguistics components contribute around 50% in scoring a composition. In scoring a composition, content takes 30% for the scoring, organization takes 20% for the scoring, vocabulary takes 20% for the scoring, language use takes 25% for the scoring, and mechanical takes 5% for the scoring. It can be concluded that in writing a good composition, we need not only good content and organization but also good vocabulary, language use, and mechanical (linguistics components). Some studies about error analysis on the students’ compositions have been conducted. Most of them have shown that many students still make errors on their compositions. Gustilo and Magno (2012) investigated the sentence level errors in one hundred fifty essays written by freshmen college students in five private schools in Metro Manila, Philippine. They found that the top five errors which occur in the essays were comma (unnecessary or missing comma, missing comma after an introductory clause or phrase, and missing comma before a non-restrictive clause), word choice (wrong word form/word choice), verbs (s-v agreement, verb tense, and verb form), capitalization and punctuation, and sentence structure (fragment and run on sentences). Then, AbiSamra (2003) analyzed ten written works of Arabian students which were collected in their mid-term examination. The result showed that there were some errors which found in the ten students’ essays. They were grammatical, 35 syntactic, lexical, semantic, and substance (mechanics & spelling) errors. In addition, Abushihab, El-Omari, and Tobat (2011) conducted a study to investigate and classify the grammatical errors in the writings of sixty two students of the Department of English Literature and Translation in one of private universities in Jordan. The students enrolled in a paragraph writing course in the first semester of the academic year 2009/2010. These errors were classified into six major categories: tenses, prepositions, articles, active and passive voice, verbs, and morphological errors. They found 345 grammatical errors in the students’ paragraphs. It was observed that the largest number of errors was the errors of preposition. The next problematic areas were morphological errors, articles, verbs, active and passive voice, and tenses. From the previous studies above, it can be concluded that error analysis can indicate the students’ competence in writing since it shows the area of students’ problems in writing. After discovering these areas, the teachers can take some better treatments and more reinforcements, so it can be a feedback for the students and they can use it to develop their writing competence. Gustilo and Magno (2012) states that errors can be viewed as valuable information for the teachers, the researchers, and the students. For the teachers, it provides information about the students' errors which helps them to correct the students' errors and improves the effectiveness of their teaching. For the researchers, it gives them valuable data and information about how language is acquired or learned. Then, for the students, it enables them to reflect on their learning, so they can get feedback and develop their competence. In addition, Erdogan (2005) concludes that error analysis can identify the strategies that language learners use, find out the reason of the students’ errors, determine the common difficulties in learning, and help teachers to develop materials for remedial teaching. Looking at the huge benefits of error analysis, the researcher is interested in conducting a study about analyzing errors in the students’ compositions. Besides, the researcher had ever visited a library and read one of the English Department student’s theses submitted there. She found that there were still any errors found in that thesis. That is why; she wants to analyze the theses of the English Department’s students in one of state universities in Surabaya, Indonesia. She does not analyze all of the parts of the thesis, but only the background of the study of the thesis. She chooses to analyze the background of the study because it becomes the foundation, reason, and explanation why they conduct the study. In this case, the students in the English Department have taken Writing I, Writing II, Writing III, Academic Writing I, Academic Writing II, and Thesis Proposal before composing the thesis. Besides, they also had been taught how to write when they were in junior and senior high school. Therefore, it can be said that they have had enough knowledge about writing to compose their thesis. Looking at this fact, she is more curious whether there are errors found in the other students’ theses, especially in the background of the study, or not. At least, the present study is intended to investigate the following problem: How are the profile of errors made by the university students in their theses’ background of the study? In line with Touchie, Ferris (2005) as cited in Kato (2006) also includes all linguistics components in analyzing the students’ compositions. She divides the common writing errors which occur in the students’ compositions into four categories: 1) morphological, 2) lexical, 3) syntactic, and 4) mechanical errors. Morphological errors are errors which include the lack of grammatical processes of inflection and derivation, e.g. My brother is fattest than my sister (My brother is fatter than my sister). Lexical errors are errors which involve inappropriate direct translation from the learner’s native language or the use of wrong lexical items in the second language, e.g. I will wait you when the clock is five (I will wait you at five o’clock). Syntactic errors are errors in sentence/clause boundaries (run-ons, fragments, and comma splices), word order, and other ungrammatical sentence constructions, e.g. Rini very beautiful (Rini is very beautiful). Then, Mechanical errors are errors in using punctuation, spelling, and capitalization, e.g. i will go to jakarta next week buying a refrigenerator (I will go to Jakarta next week to buy a refrigerator.) Based on these categories, the researcher formulates the research questions of this study as follows: (1) How are the profiles of morphological errors made by the university students in their theses’ background of the study? (2) How are the profiles of lexical errors made by the university students in their theses’ background of the study? (3) How are the profiles of syntactic errors made by the university students in their theses’ background of the study? (4) How are the profiles of mechanical errors made by the university students in their theses’ background of the study? METHOD This study was qualitative, especially descriptive qualitative. This design was used because the data of the study were in the form of words in written language rather than numbers, taken in natural setting, and explained descriptively. In this study, the researcher analyzed the English Department students’ theses background of the study, which were submitted in the Language and Art Faculty library, to know the profile of morphological, lexical, syntactic, and mechanical errors. The data were analyzed and interpreted based on Ferris’s error analysis model which categorized common writing errors into four categories: morphological, lexical, syntactic, and mechanical errors. The subject of this research is the English Department students of Surabaya State University who have graduated from the English Department and submitted their theses in the Language and Art Faculty library. In this case, the subjects had taken Writing I, Writing II, Writing III, Academic Writing I, Academic Writing II, and Thesis Proposal before composing the thesis. Besides, they also had been taught how to write when they were in junior and senior high school. Therefore, it can be said that they have had enough knowledge about writing to compose their thesis. Besides, their theses had been approved as their graduation requirement. In this study, the researcher chose six theses from thousands theses submitted in Language and Art Faculty library randomly. She took the theses from three groups. She took two theses from the students who graduated earlier (less than four years), two theses from the students who graduated on time (four years), and two theses from the students who graduated late (more than four years). She chose theses from the students who had different time of graduation since she wanted to know the differences between the errors they committed and for heterogeneity of the subject. The sources of data in this study were the theses’ background of the study made by the English Department students which were taken from the Language and Art Faculty library. The data of the study were the sentences which contained of morphological, lexical, syntactic, and mechanical errors found in the students’ background of the study. In this study, the researcher was the key instrument in collecting data. She went to the library to choose six theses which would be analyzed. After getting the theses, she copied all of the theses’ background of the study, read, and identified the errors found in the students’ background of the study. In analyzing the data, the researcher analyzed theses’ background of the study using several steps. After identifying the errors, she classified them based on Ferris’s error analysis model which categorized common writing errors into four categories: morphological, lexical, syntactic, and mechanical errors. After classifying the errors, in order to answer the research questions about the profile of morphological, lexical, syntactic, and mechanical errors made by the university students in their theses background of the study, she did the second classification. She classified the errors into some subcategories. For the morphological errors, the classification is done in the verb errors and noun errors. Verb errors consist of verb tense, verb form, and subject - verb agreement. Then, noun errors consist of articles/determiners and noun ending (plural and possessive). For the lexical errors, the classification is done in the word choice, word form, preposition errors, pronoun errors, and spelling errors. For the syntactic errors, the classification is done in the word order, omitted word/phrase, unnecessary word/phrase, run-on sentence, and fragments/incomplete sentence. For the mechanical errors, the classification is done in capitalization, spelling, and punctuation. After classifying the errors into some subcategories, the researcher described and evaluated the errors found to make conclusion from the result of the analysis. RESULT AND DISCUSSION The Profiles of Morphological Errors Made by the University Students in Their Theses’ Background of the Study In this study, the classification of the morphological errors is done on the verb error and noun error. Verb error consists of verb tense, verb form, and subject - verb agreement. Then, noun error consists of articles/determiners and noun ending (plural and possessive). The further descriptions are explained below: Verb Error Subcategory Based on the Ferris’s error analysis model, verb error subcategory consists of errors in verb tense, verb form (infinitive, gerund and other forms), and relevant subject-verb agreement. The following description explains the students’ errors in verb errors subcategory from each group. A. Verb Tenses Error According to Ehrlich and Murphy (1991:49), verb tense can be the indicator of time when an action takes place. Therefore, we can indicate whether somebody writes or speaks about past, present, or future events from the tenses that he/she uses. There are some tenses in English, such as present, past, past perfect, present perfect, future, future perfect, etc. On the contrary, in the other languages, include the students’ native language, there is no different tenses when somebody writes or speaks about past, present, or future events; the verbs that he/she uses are always in the same form. Therefore, most of the verb tense errors in this study were interlingual errors. Touchie (1986: 77-79) states that interlingual errors are errors due to the influence of the native language. In this study, because in the students’ native language the verbs that the students use are always in the same form, they confused in using it since it’s different to their native language. From the verb tenses errors which were found, most of the students from each group failed to identify the correct pattern of simple present tense. Here were some examples of verb tenses errors : [1] ...without realizing that they have master several vocabulary and expressions in English. [2] The presented material was made by the students, the teacher only prepare some examples for them, and then they have to make their text as they want with the guidance from the teacher and their friends. (Student 1) In sentence [1], the student failed to identify the correct pattern of present perfect tense since he used simple present instead of the present perfect continuous. The verb in the present perfect tense should be in past participle (V3), but in this case he used simple form (V1). Therefore, the sentence should be: “...without realizing that they have mastered several vocabularies and expressions in English.” Then, in sentence [2], he failed to identify the correct pattern of present tense; he should use to be for simple present tense (is) instead of to be for past tense (was). Besides, the second subject (the teacher) was singular. In simple present tense, the students should add verb ending –s or –es if the subject is singular. Therefore, the correct sentence should be: “The presented material is made by the students, the teacher only prepares some examples for them, and then they have to make their texts as they want with the guidance from the teacher and their friends.” [3] Nowadays, the curriculum that we used is the 2006 English standard competence. (Student 3) [4] Realia are things that given an explanation about real life. (Student 4) In sentence [3], the student failed to identify the correct pattern of present tense. The verb in the present tense should be in the simple present form (V1), but in this case she used verb in the form of simple past (V2). Therefore, the sentence should be: “Nowadays, the curriculum that we use is the 2006 English Standard Competence.” In sentence [4], the student also failed to identify the correct pattern of present tense. He used verb in the form of past participle (V3) instead of simple form (V1). Thus, the sentence should be: “Realia are things that give an explanation about real life.” [5] A teacher could make the end goals of language learning seem nearer and more motivating. (Student 5) [6] Lado (1957:2) says that the students who came in contact with a foreign language will face some features.... [7] Dulay (1989:138) stated that making error is an inevitable part of learning. (Student 6) In sentence [5], [6], and [7], the students also failed to identify the correct pattern of present tense. The verb in the present tense should be in the simple present form (V1), but in these cases they used verb in the form of simple past (V2). Therefore, the sentence should be: [6] A teacher can make the end goals of language learning seem nearer and more motivating. [7] Lado (1957:2) says that the students who come in contact with a foreign language will face some features....and [8] Dulay (1989:138) states that making error is an inevitable part of learning.” B. Verb Form Error Verb form errors occur when the students cannot apply the rule of gerund, infinitive, and past voice well. Azar (1992:150) states that a gerund is an “ing” verb form used as a noun whereas an infinitive is a verb form which is preceded by “to” and its function is as noun, adjective or adverb. Then, in passive voice, the object of an active verb becomes the subject of the passive verb. Most of the students made errors in verb form errors because of overgeneralization. Overgeneralization is the use of one form or construction in one context and extending its application to other contexts where it should not apply (Touchie, 1986: 77-79). Here were some examples of verb form errors: [8] ...the students are expected to be mastered in four skills listening, speaking, reading and writing. [9] ... in speaking people put idea into words, talking about perception, feeling and intension. (Student 4) In sentence [8], the students failed to apply the rule in passive voice and infinitive. He should omit be and verb ending –ed. Therefore, the correct sentence should be: “...the students are expected to master the four skills: listening, speaking, reading and writing.” In sentence [9], the first verb (put) is in the simple form (V1), so in the parallel structure, the second verb should in simple form (talk), not in gerund (talking). Therefore, the correct sentence should be: “... in speaking people put idea into words, talk about perception, feeling and intension.” [10] They require choosing the proper method. (Student 5) [11] Oshima and Hogue (1991:2) defined that academic writing is a kind of students writing that require doing in school, college or university. (Student 6) In sentence [10] and [11], require is one of verbs that is followed by a noun + an infinitive. But in these cases, the students applied the rule of gerund in it. This cause of error was called overgeneralization. Besides, these sentences also should be in passive voice not in active voice. Therefore, the sentences should be: [10] They are required to choose the proper method. And [11] Oshima and Hogue (1991:2) define that academic writing is a kind of students’ writing that is required to do by the students in school, college or university. C. Subject-Verb Agreement Error The subject–verb agreement occurs when the verb of a sentence does not match with the subject in number and in person. The students in every group made subject-verb agreement errors in their composition. It took place because in the students’ native language, there was no subject-verb agreement. They use same verb for singular or plural subject. Some examples of error in subject-verb agreement from each group were: [12] So improving participation is an obvious goal in courses that include frequent discussions and small-group work. (Student 1) [13] The key feature of successful teaching receptive skills such as reading is the teacher concern on the comprehension... (Student 2) In sentence [12] and [13], the subjects were singular (improving participation, and the teacher), but the students tended to omit the verbal ending –s or –es in those sentences. Therefore, the correct sentences should be: “So improving participation is an obvious goal in courses that includes frequent discussions and small-group work.” and “The key feature of successful teaching receptive skills such as reading is the teacher concerns on the comprehension...” [14] It means that reading ability is very important and teaching reading need much time in the school environment. [15] The government need to seek the most appropriate curriculum. (Student 3) [16] The second, Student are usually bored with the classroom, because sometimes the teacher manage the the classroom monotonously. [17] Baker and Westrup (2003:5) states “students find it difficult to have conversation on a topic that they know little about.” (Student 4) In sentence [14], [15], and [16], the subjects were also singular (teaching reading, government, and the teacher) but the students tended to omit the verbal ending –s or –es in those sentences. Therefore, the correct sentences should be: [14] It means that reading ability is very important and teaching reading needs much time in the school environment. [15] The government needs to seek the most appropriate curriculum. [16] The second, the students are usually bored with the classroom because sometimes the teacher manages the classroom monotonously. In contrary, in sentence [17], the subject was plural (Baker and Westrup), but the student added the verbal ending –s. He should omit it in order the subject matched with the verb. Therefore, the correct sentences should be: “Baker and Westrup (2003:5) state that “students find it difficult to have conversation on a topic that they know little about.” [18] The teacher needs to find the exact approach, methods, and technique which is suitable for the junior high school students. (Student 5) [19] Students tends to make errors when they are studying a language. (Student 6) In sentence [18], the student misused of to be. The adjective clause “which is suitable for the junior high school student” was modified the noun “the exact approach, methods, and technique”. Here, the noun was plural, so the correct sentence should be: “The teacher needs to find the exact approach, methods, and technique which are suitable for the junior high school students.” In sentence [19], the subject were plural (students), but the student added the verbal ending –s. He should omit it in order the subject matched with the verb. Therefore, the correct sentences should be:” Students tend to make errors when they are studying a language.” Noun Error Subcategory In the morphological errors category, noun errors consist of article/determine errors and ending noun errors. A. Article/Determiner Errors According to Bryant (1984), article/determiner errors are frequently encountered by Asian students since definite and indefinite articles do not exist in their languages. In these languages, the noun stands alone, often being modified only by descriptive and/or limiting adjectives (possessive adjectives, relative adjectives, interrogative adjectives, demonstrative adjectives, and indefinite adjectives). This statement was proven in this study, the students from all group made article/determiner errors, especially for misused of zero article (Ø) for the since in their native language (Indonesia) definite and indefinite articles do not exist. In this study the article/determiner errors were one of the most problematic errors faced by the students. It was in line with Han et al (2006:115) in Apriyanti (2013) who state that, “one of the most difficult challenges faced by non-native speakers of English is mastering the system of English articles. Here were some examples of article/determiner errors made by the students: [20] ...the teacher could not maximize students’ participation in learning and practicing the competence... [21] Although it is not easy to make students speak as the teacher wants... (Student 1) [22] Nowadays, English is taught formally in fourth graders of elementary school... [23] Moreover, to be a good reader, students need to be strategic readers first... (Student 2) In sentence [20] and [21], the words student’ participation and students had been identified before by the writers. Then, in sentence [22], the word fourth graders was involving an ordinal form to show order/level. Therefore, according to its characteristics and the rules of using article the, these nouns needed the article the before those words. In sentence [23], the student should not use article a since the subject is plural (students). Therefore, the correct sentence should be: “Moreover, to be good readers, students need to be strategic readers first...” [24] It is an important component because it can be used as resource for teachers in teaching and learning process. (Student 3) [25] So, in the end of study, students are expected to have competence to communicate fluently... (Student 4) In sentence [24] and [25], the words teachers and students had been identified before by the writers. Then, according to its characteristics and the rules of using article the proposed by Azar (1999:115), these nouns needed the article the before those words. [26] For example, the invention of internet, mobile phone, etc.... [27] In functional level, students use language to fulfill the daily life, for example reading the newspaper, manual or direction. (Student 5) [28] The main function of teaching English as stated in 1994 curriculum is to enable students to acquire science... (Student 6) In sentence [26], internet and mobile phone are kinds of invention. In sentence [27], the words functional level had been identified before by the writers. Then, in sentence [28], the word 1994 curriculum is a specific thing. Therefore, according to its characteristics and the rules on using article the, these nouns needed the article the. B. Noun Ending Error Noun ending errors are divided into noun ending error in plural and possessive. In this case, the students made noun ending errors since in their native language, the rule of pluralization is different from the rule of pluralization in English. In Indonesian, when the noun is plural, it is indicated by the amount of the noun, whereas in English they should add –s or –es after the noun to show the pluralization. Then, in Indonesian, there are some words that show about possessive, such as –nya, -ku, mu, etc, whereas in English they must use appostrophe and noun ending –s or –es to show possessive. Here were some examples of noun ending errors : [29] Therefore it is important for the teacher to be able to manage active student participation... [30] Teacher and students activities are clearly mentioned, but it is quite difficult to understand and follow. (Student 1) In sentence [29], the student omitted the apostrophe and noun ending -s after the word student to show possession. Therefore, this sentence should be: “Therefore, it is important for the teacher to be able to manage active student’s participation...” In sentence [30], he also omitted the apostrophe after the word students to show possession. Therefore, this sentence should be: “The teacher and the students’ activities are clearly mentioned, but they are quite difficult to understand and follow.” [31] Celce-Murcia at al in Agustien (2004:2) explains five component of communicative communication... [32] ...most of the student will be interested if the students are in condition that make students comfort in the class. (Student 4) In sentence [31], the noun was plural but the students omitted noun ending –s after the word component. Thus, the correct sentence should be: “Celce-Murcia et al in Agustien (2004:2) explain five components of communicative communication...” In sentence [32], most of was an expression of quantity. It preceded specific plural count noun or noun count noun. Since the student was count noun, it should be in plural form. Therefore, the correct sentence should be: “...most of the students will be interested if the students are in condition that makes students comfort in the class.” [33] As a foreign language it is taught and learned, either formally or informally in many part of our country... (Student 6) In sentence [33], the word many showed the expressions of quantity. A noun which is preceded by some and many should be in plural form. Therefore, the correct sentences should be: “As a foreign language, it is taught and learned either formally or informally in many parts of our country...” The Profiles of Lexical Errors Made by the University Students in Their Theses’ Background of the Study In this study, lexical errors consist of all errors in word choice, word form, preposition errors, pronoun errors and spelling errors. Spelling errors are included if only in misspelling resulted in an actual English word. Word Choice Errors Students usually encounter some difficulties when they write a composition. One of problems is lack of vocabulary. It makes the students unable to choose appropriate word for their sentences. Consequently, they make errors in word choice. In this study, most of the students made word choice errors in their theses’ background of the study. Some examples of those errors were: [34] There are 32 students with most of them are female students. [35] ...the students who did not get the change to present their narrative on the previous meeting must present on the second meeting. (Student 1) [36] Besides that, the extension of scientific books in English language makes students have to master reading skill. (Student 2) In sentence [34], the student should not use preposition with. He should use adjective clause to modify the noun students. In sentence [35], the word change that was used by the student was not appropriate. He should use the word chance in this sentence. In sentence [36], besides that is usually used in spoken language, but the student overgeneralize it and apply it in written language. The student should use besides in formal written language. Therefore, the correct sentences should be: [34] There are 32 students which most of them are female students. [35]...the students who did not get the chance to present their narrative on the previous meeting must present on the second meeting. [36] Besides, the extension of scientific books in English language makes students have to master reading skill. [37] An English text book, in which the ninth graders students used, has to fulfill the 2006 English Standard Competence of BSNP [38] The researcher is concerned on analyzing the reading material in “English In Focus” for the ninth of Junior High School... (Student 3) [39] Schunke (1988:295) states that realia are tangible objects things that can be seen touch held and smelled that gives students a real life experience with the topic they have been studying... (Student 4) In sentence [37] and [38], the student should use the ninth graders instead of the ninth graders students or the ninth to show the students’ grade at school. In sentence [39], the word objects and things are synonymous, so the students should choose between objects or things that can be used in that sentence. [40] In addition, English has been taught in elementary, junior, senior and university. (Student 5) In sentence [40], the bolded words elementary, junior, senior are ambiguous. The student should make it clear by changing the words into elementary school, junior high school, and senior high school. Word Form Errors In this study, there were two word form errors made by the student. It was committed by the student who graduated on time. [41] “the goal of classroom management is to creat classroom atmosphare conducive to interact in English meaningful.” [42] So, the teacher can use realia as an alternative technique in teaching speaking and narrative oral production skill about fable can help student more interest to speak. (Student 4) In sentence [41], the student overgeneralized the use of part of speech, he should use adverb instead of adjective in this sentence. In sentence [42], he should use adjective instead of noun. Therefore, the correct sentence should be: “the goal of classroom management is to create conducive classroom atmosphere to interact in English meaningfully.” And “So the teacher can use realia as an alternative technique in teaching speaking, and narrative oral production skill about fable can help the student more interested to speak.” Preposition Error In English, there are so many prepositions and it has different uses and rules. Therefore, when the students misused, omitted, misplaced or added preposition in their sentence wrongly, preposition errors occur. Some examples of preposition errors in the students’ compositions were: [43] ...then let them to answer the question related with the text. (Student 2) In sentence [43], the student misused preposition after adjective related. It should be combined using preposition to instead of with. Therefore, the correct sentence should be: “...then let them to answer the question related to the text.” [44] ...this skill is very important to be practiced for student in the classroom. [45] However, the student will interest make the realia in attractive situation with story and narrative text is one of text types that provide attractive and experience situation (Student 4) In sentence [44], the student misused of preposition for. He should use preposition by since this sentence was passive form. Therefore, the correct sentence should be: “...this skill is very important to be practiced by student in the classroom.” In sentence [45], the student failed to apply the correct pattern of passive voice. Besides, he omitted preposition in after the word interest. Therefore, the correct sentence should be: “However, the student will be interested in making the realia in attractive situation with story and narrative text is one of text types that provides attractive and experience situation.” [46] ...the students are able to communicate fluently oral and written form. (Student 6) In sentence [46], the students omitted preposition in. Therefore, the correct sentence should be: “...the students are able to communicate fluently in oral and written form. Pronoun Errors Pronoun errors took place when the students misused, misplaced, or omitted pronoun in their sentences. Some examples of pronoun errors in the students’ compositions were: [47] Teacher and students activities are clearly mentioned, but it is quite difficult to understand and follow. (Student 1) In sentence [47], the subject was plural (teacher and students’ activities), so the student should use personal pronoun they instead of it. Therefore, the correct sentence should be: “Teacher and students’ activities are clearly mentioned, but it is quite difficult to understand and follow.” [48] When the learner learns the target language, he will face more problems than they learn his own mother tongue [49] Errors made by the students can be identified as evidences that he is in the process of learning. (Student 6) In sentence [48], the subject is singular (learner), so the student should use personal pronoun he instead of they. In sentence [49], the subject is plural (the students), so the student should use they as the personal pronoun. Therefore, the correct sentence should be: “When the learner learns the target language, he will face more problems than when he learns his own mother tongue.” and “Errors made by the students can be identified as evidences that they are in the process of learning.” Spelling Errors In lexical error, spelling errors are included when they produce an actual English word or the combination of two actual English words. [50] Therefore, a good textbook should fullfill the standard competence and relevant to the curriculum. [51] But the teacher should be carefull and review the text book when choosing a book... (Student 3) [52] Therefor a teacher has to make variation in the ways of his or her teaching. (Student 4) In sentence [50] and [51], the word fullfill and carefull were spelling errors since the student added the letter l in the actual words. It was caused by overgeneralization since she thought that the word full in English always had double l , so she added letter l in words fulfill and careful. Therefore, the correct words were fulfill and careful. In sentence [52], the student omitted the letter e in the actual words. The correct word should be therefore. Those spelling errors are categorized as lexical error since they are combination of two actual English words. [53] It can be seen trough the science and technology development. (Student 5) In sentence [53], the word trough was a spelling error since the student omitted the letter h in the word through. This spelling error produced an actual English word trough .Therefore, it categorized as lexical error. The Profiles of Syntactic Errors Made by the University Students in Their Theses’ Background of the Study The classification of syntactic error is done in the word order, omitted word/phrase, unnecessary word/phrase, run-on sentence, and fragments/incomplete sentence. Unidiomatic sentence constructions were not included in this study since they were not found in all students’ compositions. Error in Word Order Word order refers to the order in which elements occur in a clause or sentence (Leech, 2006:126). Word order in English sometimes makes the students confused since it is different from their native language. The ordering of words in English is in reverse order to their native language (Indonesian). The following description explained the students’ errors in word order from each group. [54] The result is at best highly imperfect translation, at worst frustation and incomprehension. (Student 3) [55] ...“the goal of classroom management is to creat classroom atmosphare conducive to interact in English meaningful.” (Student 4) In sentence [54] and [55], the students could not order the words very well. The correct sentences should be: “The best result is highly imperfect translation and the worst are frustration and incomprehension.” And “...the goal of classroom management is to create conducive classroom atmosphere to interact in English meaningfully.” Error in Omitted Word/Phrase Error in omitted word/phrase took place since the students omitted a word/phrase or some word/phrase in their sentences. The examples of error in omitted word/phrase found in the students’ composition were: [56] English is an international language plays an important role to all aspects of human life. (Student 3) [57] Depdiknas (2004:30) states the English learning in senior high school is targeted to the learners in order to gain the functional level... [58] They have to communicate through speaking to gain much more information with their teacher friends in order to practice and improve their speaking skill. (Student 4) In sentence [56], the student omitted the subject pronoun which. This word modified the noun English. In sentence [57], the word states should be followed by that, but in this sentence the student omitted it. In sentence [58], He also omitted conjunction and to connect the words teacher and friends. Therefore, the correct sentences should be: “English is an international language which plays an important role to all aspects of human life”, “Depdiknas (2004:30) states that the English learning in senior high school is targeted to the learners in order to gain the functional level...” and “They have to communicate through speaking to gain much more information with their teacher and friends in order to practice and improve their speaking skill.” [59] While the fact shows most of the teachers might not implement it in depth study... (Student 5) [60] According Brown (1980:41), the learning of foreign language (English) often meets a lot of difficulties. (Student 6) In sentence [59], the word shows should be followed by that and in sentence [60], the word according should be followed by to but in these sentences the students omitted those words. Therefore the correct sentence should be: “While the fact shows that most of the teachers might not implement it in depth study...” and “According to Brown (1980:41), the learning of foreign language (English) often meets a lot of difficulties.” Error in Unnecessary Word/Phrase Error in unnecessary word/phrase took place since the students added a word/phrase or some word/phrase which were unnecessary in their sentences. The examples of error in omitted word/phrase found in the students’ composition were: [61] Speaking, one of skills that is very important thing in daily communication. [62] According to Chastain (1976:340) states that “Vocabulary is needed for the students to talk about some aspect of their lives.” (Student 4) In sentence [61], there was an unnecessary word. The students should omit the noun thing since the word important had modified the word skills. In sentence [62], the student should choose between according to or states that since those words could not be used together. Therefore, the sentences should be: [61] Speaking is one of skills that is very important in daily communication. And [62] Chastain (1976:340) states that “vocabulary is needed for the students to talk about some aspect of their lives.” [63] Writing is very important in the academic level, in as much as the students works are mostly in the written form. (Student 6) In sentence [63], the student should omit in much as since it was unnecessary and make the reader confused. Therefore, the correct sentence should be: Writing is very important in the academic level as the students’ works are mostly in the written form. Run-On Sentence A run-on sentence is two or more independent clauses improperly strung together. It omits the connectors, for examples semicolon or a coordinate conjunction, and often uses comma (comma slice) or a conjunctive adverb by mistake. In this study, run-on sentences were still found. It showed that the students could not join two or more independent clauses using conjunction or punctuation correctly. It could be caused by inadequate learning. Inadequate learning is caused by ignorance of rule restrictions or under differentiation and incomplete learning (Touchie, 1986: 77-79). Students in Indonesia seldom have enough knowledge about run-on sentences since most of the teachers in Indonesia seldom warn their students about it, so they have no sufficient knowledge about it. Here were some examples of run-on sentences made by each group: [64] The class is clear enough, with clear sunlight from the windows, there is no fan or AC, but the air is not too hot, the chairs and tables are arranged perfectly by the students. [65] The activity to practice the speaking skill which was conducted by the teacher and students was storytelling, the students did monologue of narrative text individually. (Student 1) In sentence [64], there were three independent clauses and in sentence [65] there were two independent clauses. In these sentences, the student only joined those independent clauses using comma, so run-on sentence take placed. He should use a period or a semicolon between the independent clauses. Therefore, the sentences should be: [64] The class is clear enough with clear sunlight from the windows. There is no fan or AC, but the air is not too hot. The chairs and tables are arranged perfectly by the students. And [65] The activity to practice the speaking skill which was conducted by the teacher and students was storytelling; the students did monologue of narrative text individually. [66] The purpose of the teaching of English for Senior High School is to master informational competency, this purpose should be taken into account in order to make the students be able to access the knowledge in the academic purpose. [67] Realia that be used to teach speaking of narrative text can raise the students’ interest, they can be used to break up the routine class activity and they can provide fun for student in different interpretation. (Student 4) In sentence [66] and [67], there were two independent clauses. In these sentences, the student also joined those independent clauses using comma, so run-on sentence take placed. He should use a period or a semicolon between the independent clauses. Therefore, the sentences should be: [66] The purpose of the teaching of English for Senior High School is to master informational competency. This purpose should be taken into account in order to make the students be able to access the knowledge in the academic purpose. And [67] Realia that are used to teach speaking of narrative text can raise the students’ interest. They can be used to break up the routine class activity and provide fun for the student in different interpretation. [68] An academic writing has special audience that is the academic circle, the advisors and the students, it is formal and serious in tone, and its purpose is to explain. (Student 6) In sentence [68], run-on sentence occurred since the student joined two independent clauses using comma. He should use a period or a semicolon between the independent clauses. Therefore, the sentences should be: “An academic writing has special audiences that are the academic circle, the advisors and the students. It is formal and serious in tone, and its purpose is to explain.” Fragments Sentence fragment is a group of words without a subject or predicate in an independent clause. It is usually called as incomplete sentence since a complete sentence in English must has at least a subject and a predicate. [69] ...and the recent Level of Educational Unit Curriculum (2006-present) [70] ...the objective of the reading skill on the ninth graders are expected to be able to understand the meaning of short functional text and short simple essay text, in the form of procedure, narrative and report in daily life context... (Student 3) [71] Speaking, one of skills that is very important thing in daily communication. (Student 4) Sentence [69] and [71] were fragments since there was no verb in these sentences. Therefore, the students should add to be in these sentences and the correct sentences should be: “...and the recent is Level of Educational Unit Curriculum (2006-present)” and “Speaking is one of skills that is very important in daily communication. Sentence [70] was fragment since it had no object. The object should be placed after the word expecting. Therefore, the correct sentence should be: “...the objective of the reading skill on the ninth graders are expecting the students to be able to understand the meaning